Peran Literasi Budaya Dan Kewarganegaraan Dalam Pembentukan Karakter Peserta Didik Sekolah Menengah Atas - Rahma Siregar; Suhdi Ansah Batubara; Indra Wahyudi; Nur Kholijah; Nur Aisyah Dlt; Tuty Awaliyah Pohan; Robiatul Adawitah Ray; Evi Sandelilah; Nanda Fitriani; Eva Suryani; Royhan Ansori Nasution; Resdilla Pratiwi (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Cultural and civic literacy play a crucial role in character development for high school students amidst the challenges of the digital era and globalization. This study aims to examine the synergy between cultural and civic literacy in shaping student character. The study employed a qualitative approach through literature review supported by limited observations and interviews at SMA Negeri 3 Panyabungan. The results indicate that cultural and civic literacy contribute positively to student character development, including discipline, responsibility, tolerance, democratic attitudes, and nationalism. Its implementation is evident through civics (PPKn) learning and the instilling of school culture. The novelty of this study lies in strengthening the synergy between cultural and civic literacy linked to local Mandailing cultural values, thus making student character formation more contextual and applicable.